Enhancing Conceptual Understanding of Mechanics through Smartphone-Based Laboratories: A Quasi-Experimental Study with First-Year University Students - Meseret Tadesse Bekele (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2014)
Introductory mechanics courses present persistent challenges for first-year university students, who often hold robust misconceptions that traditional instruction fails to address. Smartphone-based laboratories (SmartIPLs) offer an accessible, low-cost alternative that may enhance conceptual understanding through authentic, inquiry-based experimentation. This quasi-experimental study investigated the effectiveness of smartphone-based laboratories for enhancing conceptual understanding of mechanics among first-year university students and examined gender differences in intervention outcomes. Methods: Participants were 128 first-year students (45% female, 55% male) randomly assigned to experimental (n = 64) and control (n = 64) groups. The experimental group completed five smartphone-based laboratory activities using the phyphox app over eight weeks, while the control group completed traditional verification laboratories covering identical mechanics topics. Conceptual understanding was measured using the Force Concept Inventory (FCI) at pretest and posttest. Student perceptions were assessed through a 12-item survey and focus group interviews. Data were analyzed using ANCOVA, two-way ANOVA, and thematic analysis.